Skuteczność prawa i problemy jej badania: [Efficacy of law and problems connected with studying it] (Studia Prawnicze / The Legal Studies, 2023)
Any action shall be efficacious when it attains in a sufficiently high degree the purposes defined by a person undertaking it. From this point of view we may also discuss the efficacy of law (of a legal rule, of a group of legal rules, of a system of law) being a result of a purposful activity of a legislator. The Au- thor presents an analysis of the efficacy of law understood as prohibitive and imperative rules, with the assumption that the purpose of the legislator was sufficiently precisely defined.As a basis for the typology of the efficacy of law a differentiation was made between: direct purposes (i.e. conduct conformable to a rule) and indirect pur- poses (consequences of the conduct conformable to a rule) as well as between subjective purposes (i.e. behaviour, feelings and attitudes) and objective purposes (other purposes).Psychological efficacy of law means the influence of the information about a given rule on feelings and attitudes of an addressee of the rule regardless of whether this leads to conduct conformable to a rule or not. Behavioural efficacy means that a direct purpose of a given rule is realized because the information about this rule motivated its addressee. Finite efficacy means that an indirect objective purpose is attained, in another words, that a definite situation being a consequence of the attainment of the direct purpose is created. Socio-educational efficacy or law means attainment of the subjective indirect purpose by evoking certain attitudes, of an addressee of legal rules or of other persons.The Autor presents an analysis of assumptions and conditions to be made while studying the above mentioned kinds of the efficacy of law. Preparing scales with the aim of measuring each of these kinds of efficacy needs meeting various complex conditions. Because of the difficulties, in practice partial indica- tors of the efficacy of law are commonly used. A typical one to cite is a quan- titative analysis of conducts contrary to the law, the constatation of which is an assumed function of the organs applying the law.